Participatory research methods for technology evaluation: a manual for scientists working with farmers - Bellon, Mauricio (International Maize and Wheat Improvement Center, 2001)
This manual presents methods that enable agricultural scientist and farmers to evaluate technologies/practices jointly. The methods are specifically designed for participatory research on germplasm and soil fertility technologies, and they are illustrated with actual examples from three research projects. The manual begins by reviewing conceptual issues that are important in participatory research and presents information to assist researchers in selecting research sites and fieldwork participants. Next, the manual describes the rationale and associated methods for each major activity in farmer participatory research: diagnosing farmers’ conditions, evaluating current and new technologies/practices, and assessing their impact. Goals, procedures, advantages, and limitations of each method are outlined. The manual also presents detailed information on analyzing data gathered through participatory methods, discusses differences between gathering data through participatory methods and more traditional structured farm surveys, and offers examples, based on field experience, of the choices and strategies involved in applying these methods.